2022
DOI: 10.14309/01.ajg.0000860728.41531.11
|View full text |Cite
|
Sign up to set email alerts
|

S1022 Treatment Preferences in Crohn’s Disease Perianal Fistula: Patient Perspectives

Abstract: Figure 1. Cardiac event-free Survival in IBD cases vs. non-IBD ControlsTable 1. Demographics by IBD case/control status IBD n553 Non-IBD n5106 P-value Age 55 56 0.97 Female 18 (34%) 34 (32%) 0.81 BMI 28 27 0.99 Race: Caucasian 53 (100% 100 (94%) 0.21 Smoker 14 (26%) 28 (26%) 1 Statin use 22 (42%) 57 (46%) 0.57 Diabetes 5 (9%) 10 (9%) 1 Aspirin Use 9 (17%) 26 (25%) 0.28

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…The key findings from this study are in keeping with the core outcomes identified by Sahnan et al [ 48 ] and are comparable with the findings of a recent study in a similar patient population conducted in the United States[ 48 , 49 ]. Further research on the potential impact of age, sex, and disease severity on patients’ treatment preferences could support healthcare professionals in the clinical management and treatment decisions for CPF.…”
Section: Discussionsupporting
confidence: 91%
“…The key findings from this study are in keeping with the core outcomes identified by Sahnan et al [ 48 ] and are comparable with the findings of a recent study in a similar patient population conducted in the United States[ 48 , 49 ]. Further research on the potential impact of age, sex, and disease severity on patients’ treatment preferences could support healthcare professionals in the clinical management and treatment decisions for CPF.…”
Section: Discussionsupporting
confidence: 91%